CALCULATION OF STRUCTURES ACCORDING TO THE THEORY OF REINFORCED CONCRETE RELIABILITY - Akhmedov Islombek; Kholmirzayev Sattor; Nuritdinov Jasurbek (Journal of new century innovations, 2023)
Abstract. The impact on the reliability of buildings is the analysis of weight loss factors.